81.9k views
3 votes
Solve |3h+1|=7h
The solution is h=

User Kaufman
by
5.2k points

2 Answers

3 votes

Answer:

0.25

Explanation:

Simplifying

3h + 1 = 7h

Reorder the terms:

1 + 3h = 7h

Solving

1 + 3h = 7h

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '-7h' to each side of the equation.

1 + 3h + -7h = 7h + -7h

Combine like terms: 3h + -7h = -4h

1 + -4h = 7h + -7h

Combine like terms: 7h + -7h = 0

1 + -4h = 0

Add '-1' to each side of the equation.

1 + -1 + -4h = 0 + -1

Combine like terms: 1 + -1 = 0

0 + -4h = 0 + -1

-4h = 0 + -1

Combine like terms: 0 + -1 = -1

-4h = -1

Divide each side by '-4'.

h = 0.25

Simplifying

h = 0.25

User Rob Watts
by
5.3k points
2 votes

h equals o.25 because 4h = 1 and 1/4 = 0.25

User Eldjon
by
5.0k points